FRI0207 A phase I/II clinical trial of intra-articular administration of ARG098, an anti-FAS IGM monoclonal antibody, in knee joint synovitis of japanese patients with rheumatoid arthritis. (23rd January 2014) - Matsubara, T.; Okuda, K.; Chiba, J.; Takayama, A.; Inoue, H.; Sakurai, T.; Wakabayashi, H.; Kaneko, A.; Sugimoto, K.; Yamazaki, H.; Takanashi, T.; Takasaki, Y.; et al.
Abstract : Background: ARG098, a chimeric anti-Fas IgM monoclonal antibody, possesses a novel mode of action totally different from those of currently available RA therapeutics including cytokine targeting biologics. The Fas molecule (also known as APO-1 or CD95) mediates apoptosis in response to Fas ligand (Fas-L). Preclinical studies demonstrated that ARG098 specifically targets the Fas molecule leads to apoptosis in synoviocytes. Objectives: An open-label sequential dose-escalation study of ARG098 was conducted to assess the safety and efficacy. Methods: 43 patients diagnosed by the ACR criteria with knee joint synovitis were enrolled. The study had 7 dose groups from 0.01, 0.03, 0.1, 0.3, 1, 3 and 10 μg/knee, 6 patients in each group (7 patients in 10 μg) and single dose of ARG098 was intra-articularly administered to the target knee. Patients were required to be hospitalized at least 4 days after administration for close safety monitoring, and the assessment continued for 8 weeks with visit bases. Results: The results showed that ARG098 was well-tolerated and no serious adverse events were observed. Total 33 adverse events (AEs) in 19 patients, and drug-related AEs in 9 patients which included non-clinical hepatological and cardiological findings were confirmed, however those were occurred in low frequency and the severity was all mild. ARG098 serum concentration was below the limit of qualification level (<2.5 ng/mL). The clinical improvement was observed in most of the patients. Knee pain score by visual analogue scale (VAS) showed improvement at some assessment visits. The pain VAS of target knee was statistically improved at day 7 in 0.01 μg (-32.3±11.3 mm), day 14 and 28 in 1 μg (-27.3±19.3 mm, -27.5±19.6 mm) and day 7 and 14 in 10 μg (-37.4±26.0 mm, -35.4±26.0 mm) groups. The assessment with MRI showed improvement in more than half patients in 0.03 to 3 μg groups, and no deterioration was observed in all 43 patients. Conclusions: The safety of single intra-articular administration of ARG098 was well-confirmed up to 10 μg/knee and the pain VAS assessment and MRI showed improvements. However the dose dependency was not clearly observed. Repeat administration of ARG098 Phase IIa placebo-controlled trial is ongoing to determine the appropriate dosage and assessment methods. Disclosure of Interest: None Declared